Self-Activity Levels Among University Internal Department Supervisors - Al-Mayahy , Rawaa Jaafar Abd; Al-Anzi , Hussein Karim Mohammed (Psikologia : Jurnal Psikologi, 2025)
General Background: Self-activity represents a core psychological construct within social cognitive theory, reflecting individuals’ beliefs about their capacities to manage tasks and challenges. Specific Background: In university internal departments, supervisors play a pivotal role in fostering student stability and institutional functioning, making their self-activity particularly relevant. Knowledge Gap: Despite its importance, limited empirical evidence addresses self-activity among internal department supervisors in the Iraqi university context. Aim: This study examined the level of self-activity among supervisors at Wasit University and explored gender-based differences. Methods and Results: Using a stratified random sample of 150 supervisors, a 30-item scale grounded in Kurtus’s framework (physical, mental, and emotional dimensions) was developed and validated. Findings indicated a high level of self-activity (M = 95.98) significantly exceeding the hypothetical mean, with no statistically significant gender differences. Novelty: The study provides a culturally contextualized, psychometrically validated measure tailored to Iraqi supervisors. Implications: Results underscore the importance of institutional support and professional development programs to sustain supervisors’ psychological vitality and performance quality. Highlights: Supervisors demonstrated high physical, mental, and emotional self-activity. No statistically significant gender differences were identified. The study offers a validated self-activity scale for Iraqi university settings. Keywords: Self-activity, Internal Department Supervisors, Social Cognitive Theory, Gender Differences, University Context